(untitled) (Cadernos de Sociomuseologia, 2009)
The South Eastern Museums Service is one of ten Area Museums Councils in Great Britain. They are partnerships; membership organizations to which the 2 000 + museums belong. They provide advice, support, technical services, information and training for their members. They are the principal channel of government grant-in-aid to local government, university and independent museums. This funding comes from the Department of National Heritage via the Museums & Galleries Commission. At the South Eastern Museums Service I am responsible for the development and delivery of training for 600 museums in our region and the provision of information about museums and of interest to museums. This paper explains how we approach in-service training and the value of the definition of national standards for our work. It will pose some questions: What is training? What is a training need? and describe a new initiative, the development of training materials and their delivery.